Integration of TAM and DeLone and McLean Models to Evaluate the Quality of NAMPAH Applications - Diana, Ros; Paputungan, Irving Vitra; Luthfi, Ahmad (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Waste banks are an important solution in environmental management, one of which is the NAMPAH application. NAMPAH is an Android-based digitalization innovation. Along with its implementation, several problems were discovered in terms of application use, especially related to the use of application systems and services. Based on this, researchers focus on system evaluation of system success. This research uses the Technology Acceptance Model (TAM) and the DeLone and McLean IS Success Model which aims to evaluate the system regarding system use. Data processing in this research used the Smart PLS 4 tool. From the research results it was found that several variables were determining factors in user satisfaction, including perceived ease of use, perceived usefulness, information quality and system quality. However, system quality is not significant to perceived usefulness. Meanwhile, service quality has an average value below the testing standards so it is not significant to user satisfaction and perceived ease of use.